Surveying the prevalence of respiratory symptoms and changes in pulmonary function parameters in workers employed in the acid wash process of a steel industry - hamidreza heidari; hoda rahimifard; mohammadreza khaksar; ahmad soltanzadeh; abolfazl mohammadbeygi; mohadese darabi; arezoo eini (طب کار, 2018)
Background & Objective: Exposure to chloride acid in industrial units can be associated with risks to the human respiratory system. The aim of this study was to investigate the respiratory symptoms and pulmonary dysfunction caused by exposure to chloride in acid washing unit of a steel industry. Materials and Methods: This cross-sectional study was a descriptive-analytic study performed in a single acid washing unit in 2017. The exposed group included 45 male workers and a reference group of 41 unexposed employees from official employees. A questionnaire was used to collect personal and occupational data and a pulmonary function test was conducted in collaboration with a physician specializing in medicine to determine the pulmonary capacity of workers. Pulmonary function parameters included FVC, FEV1 and FEV1 / FVC. T-test and chi-square were used to describe and analyze the data in SPSS. The significance level in this study was determined equal to 0.05. Results: The results showed that all parameters of lung function in exposed subjects were lower than the reference group and this difference was statistically significant for FVC and FEV1 parameters (P <0.05). The results of the investigation of respiratory tract injuries showed that the level of these injuries was higher in the exposed subjects than exposed ones (P> 0.05). Based on the results of the regression model, exposures to hydrochloric acid increased the chance of these injuries by up to 7.4 times. Conclusion: The findings of this study showed that exposure to hydrochloric acid alone could increase the risk of respiratory tract damage and pulmonary function disorders. Therefore, risk management should be considered in the face of this combination.